Quantitative Analysis of Spatial Distribution of Medial Fracture Lines in Intertrochanteric Fractures - Miaotian Tang; Hao Zhou; Gaoxiang Xu; Dake Tong; Cheng Xu; Jiantao Li (Applied Bionics and Biomechanics)
The integrity of the medial wall of the proximal femur is crucial for maintaining mechanical homeostasis. However, the impact of intertrochanteric fractures on the medial wall and the optimal diagnostic methodology remain unclear. We retrospectively analyzed CT data from 205 patients with intertrochanteric fractures. The lowest point of the medial fracture line was marked, and a standard coordinate system was established to record its spatial position. The association between AO, Evans, or Tang classification and different types of medial wall disruption was analyzed using Spearman correlation. The lowest point of the fracture line was located in the first quadrant of the proximal medial wall in 20 patients, with spatial coordinates of (6.44 ± 5.47, 6.14 ± 2.71). In 21 patients, it was in the second quadrant, with coordinates of (−7.23 ± 5.86, 8.31 ± 6.59). In 122 patients, it was in the third quadrant, with coordinates of (−9.59 ± 4.32, −24.43 ± 15.79), and in 42 patients, it was in the fourth quadrant, with coordinates of (8.18 ± 4.56, −18.20 ± 12.92). The Tang classification showed a stronger correlation with fracture instability (r = 0.40, p <0.001) compared to the AO (r = 0.32, p <0.001) and Evans (r = 0.38, p <0.001) classifications. The medial wall of the proximal femur is significantly compromised in intertrochanteric fractures, with varying mechanical stability depending on the fracture type. The Tang classification effectively differentiates these stability differences, providing valuable guidance for clinical practice.